Digital beam forming methods for variable polarimetric monopulse radar. Issue 11 (31st May 2021) - Zhang, Yi; Li, Zhangfeng; Zheng, Pei; Sun, Houjun
Abstract: In variable polarimetric monopulse radars, due to the number and types of data channels, the polarisation and angle information of the target in the receiving signals are non‐linearly coupled, which results in incorrect polarisation measurement and erroneous angle estimation through a linear digital beam forming (DBF) method. Based on a variable polarimetric monopulse radar with four channels, two non‐linear DBF methods are proposed to improve radar ability. Through the angle monopulse estimation principle and the reciprocity theorem, new pairs of summation and difference signals in all polarisation channels are formed to generate the correct polarimetric scattering and angle estimation results. The simulation and experiment results show that the proposed methods achieve a higher precision of polarisation measurement and more consistent angle estimation results compared to the linear DBF method.